Morphological variation in Black iris (Iris nigricans Dinsm.) from Jordan - Karam, N.S.=700 1 Al-Khasawneh, A.A.; Shibli, R.A.
(En, Fr, Es)
Ilus., 9 ref.
Keywords: IRIDACEAE; IRIS; FENOTIPOS; FITOMEJORAMIENTO; VARIACION GENETICA; JORDANIA; IRIS NIGRICANS; IRIS NEGRO